Vigabatrin and lamotrigine in refractory epilepsy. Issue 8 (August 1994) - Stolarek, I; Blacklaw, J; Forrest, G; Brodie, M J
Abstract : Epilepsy arises from an imbalance of inhibitory and excitatory influences in the brain. Vigabatrin (VIG) decreases the breakdown of the inhibitory neurotransmitter gamma-aminobutyric acid, whereas lamotrigine (LTG) reduces presynaptic excitatory amino acid release. 22 patients with refractory epilepsy, treated with an anticonvulsant regimen containing VIG, entered a balanced, double blind, placebo controlled, crossover trial of additional LTG. Treatment periods of 12 weeks (25 mg, 50 mg, 100 mg LTG twice daily for four weeks at each dose, and matched placebo) were followed by wash out intervals of four weeks. 14 of the 20 patients completing the study improved, resulting in a significant fall in seizure days and numbers. Analysis of seizure type confirmed a beneficial effect on partial and secondary generalised tonic-clonic seizures. At the highest LTG dose (200 mg daily) there was a median fall of 37% in seizure count with nine (45%) patients reporting > 50% reduction. Three of these patients were seizure free during this month of treatment. Side effects were minimal throughout the study. Concentrations of other antiepileptic drugs, including those of carbamazepine 10, 11-epoxide, were not modified by LTG. This study suggests a substantial efficacy for a regimen containing VIG and LTG. Combinations of drugs with complementary modes of action may provide a rational pharmacological approach to the management of refractory epilepsy.